Comorbidity of Depressive and General Anxiety Symptoms in Adolescent Survivors of Bam Earthquake (2003) with Posttraumatic Stress Disorder: A Case–Control Study - Mahdi Bina; S. Sajad Mousavi; Javad Mahmoudi-gharaei; Elham Gholampoor; Saeideh Eisar (Iranian Journal of Psychiatry, 2006)
Fax: +98-21-5419113 Objective: Several studies have shown that following disasters, major depressive disorder is the most common psychiatric disorder that occurs with posttraumatic stress disorder (PTSD). Comorbidity of anxiety symptoms have also been shown. The objective of this study was to show the comorbidity of depressive and anxiety symptoms in adolescent survivors of Bam earthquake. Method: In a case–control study, two groups of PTSD and non-PTSD Bami adolescents were assessed 7–9 months following the Bam earthquake. DSM-IV criteria and Posttraumatic Stress Scale (PSS) were used to diagnose PTSD and assess symptoms; Beck’s Depressive Inventory (BDI) and Hamilton’s Anxiety Scale were used for assessing the severity of depressive and anxiety symptoms. And the groups were compared. Results: 284 subjects were included, aged 11–18 years (mean 14.8±2.1 years). 24.3% were boys and 75.7% girls; 45.1% met criteria for PTSD. In the PTSD group, mean BDI and HAS scores were 31.4±11.7 and 22.7±10.9, respectively; in the non-PTSD group, it was respectively 20.6±12.7 and 11.8±8.1. The difference between the PTSD and non-PTSD groups was significant. There was statistical correlation between the severity of depressive and anxiety symptoms and the severity of PTSD symptoms. Conclusion: Adolescent survivors of Bam earthquake who had PTSD had more severe depressive and anxiety symptoms than the non-PTSD group, which was correlated with the severity of PTSD symptoms. PTSD may be a predictor of depressive and anxiety symptoms.